Thymic carcinoma with Lynch syndrome or microsatellite instability, a rare entity responsive to immunotherapy. (August 2021) - Repetto, M.; Conforti, F.; Pirola, S.; Calvello, M.; Pala, L.; Bonanni, B.; Catania, C.; Curigliano, G.; De Pas, T.
Abstract: Importance: Thymic carcinoma (TC) is a rare aggressive tumour occurring in adults characterised by one of the lowest tumor mutational burdens (TMB). Microsatellite instability (MSI) is a mutational signature, caused by defects in the DNA MisMatch Repair (MMR) system, that predicts benefit from immunotherapy and causes high TMB. Fragmentary and unstructured evidence of these conditions co-occurring are reported in literature. Objective: Review available data on the co-occurrence of these two conditions and determine its frequency in our institute case series. Design: We performed a systematic analysis of literature and a retrospective evaluation of all the cases of TET treated at our institution from 2000 to 2020, selecting patients with a medical history of multiple tumours to enhance a priori probability of identifying cases with underlying predisposition. Results: Literature yielded 3 cases of patients with MSI TC, for which MMR gene alteration was reported. None of them received immunotherapy. Of 366 patients with TETs treated in our institute, 32 had a medical history of multiple tumours and 25 of 32 (19 thymomas and 6 TCs) had available tissue for MMR analysis. One patient with TC showed a high TMB, and MSI due to MLH1 mutation and was treated in a phase II study with avelumab and axitinib combination obtaining a long-lasting partial response. MLH1 alterations are shared across MSI TC cases. Conclusions and relevance: This analysis highlights the usefulness of MSI testing in patients with TC. The observation of cases of TC occurring in patients with Lynch syndrome and the unexpected homogeneity of gene alterations support further investigation. Highlights: Co-occurrence of thymic carcinoma and Lynch syndrome. MSI and thymic carcinoma. Thymic carcinoma and immunotherapy.